Revitalization of Tolerance Values Through Local Cultural Traditions: Efforts to Preserve Local Culture in The Young Generation In The Traditional Game of Congklak - Azki Faisal Hamdani; Riska Anggun Fatikasari; Nasywa Azzahra; Prita Farah Dina Mayangsari; Siti Dwi Makhzumah; Alfafa Ramadhani; Nuriza Dora (International Journal of Geography, Social, and Multicultural Education, 2025)
Revitalizing tolerance values through local cultural traditions is essential in preserving local culture among the younger generation. This article explores the role of traditional games, particularly congklak, as a medium to instill tolerance and social harmony. Congklak, a traditional Indonesian game rich in historical and cultural significance, teaches important values such as patience, cooperation, and mutual respect. By integrating these values into the game’s practice, it becomes a strategic tool for fostering cultural awareness and strengthening communal bonds. This study highlights how local traditions like congklak can be revitalized to address the erosion of cultural identity in the modern era. It also emphasizes the importance of involving youth in cultural preservation efforts to ensure the sustainability of Indonesia’s intangible heritage. Through an interdisciplinary approach combining cultural studies and education, this article advocates for the incorporation of traditional games into formal and informal education systems as a means of cultivating tolerance and preserving local cultural traditions